The Importance of Social Competence Training Model Development to Improve the Performance of Elementary School Teacher Working Group - Wahira Siruwa; Abdul Hamid; H B Lukman (Journal of Innovation in Educational and Cultural Research, 2023)
The purpose of this study is to determine the form of need for a social competency training model to improve the performance of elementary school teachers. This research uses the Research Development method with a research and development design at the preliminary study stage as a needs and content analysis, the source of the data is the working group of elementary school teachers in Takalar Regency which amounts to 32 people. The results showed that: Training in communicating orally, in writing, and/or gestures; Training uses communication and information technology functionally and implements ethics, values, and norms that apply in the community in the need category. The training applies the principles of fraternity and the spirit of togetherness on average 3.82 or very much need. This means that the four indicators of teacher social competence require a training model to improve teacher performance. The results of this study contribute to providing information to educational institutions and working groups of elementary school teachers as input in conducting training and references for subsequent research.